A quantum-like model of homeopathy clinical trials: importance of in situ randomization and unblinding - Beauvais, Francis (Homeopathy, 2013)
Background: The randomized controlled trial (RCT) is the ‘gold standard’ of modern clinical pharmacology. However, for many practitioners of homeopathy, blind RCTs are an inadequate research tool for testing complex therapies such as homeopathy.Methods: Classical probabilities used in biological sciences and in medicine are only a special case of the generalized theory of probability used in quantum physics. I describe homeopathy trials using a quantum-like statistical model, a model inspired by quantum physics and taking into consideration superposition of states, non-commuting observables, probability interferences, contextuality, etc.Results: The negative effect of blinding on success of homeopathy trials and the ‘smearing effect’ (‘specific’ effects of homeopathy medicine occurring in the placebo group) are described by quantum-like probabilities without supplementary ad hoc hypotheses. The difference of positive outcome rates between placebo and homeopathy groups frequently vanish in centralized blind trials. The model proposed here suggests a way to circumvent such problems in masked homeopathy trials by incorporating in situ randomization/unblinding.Conclusion: In this quantum-like model of homeopathy clinical trials, success in open-label setting and failure with centralized blind RCTs emerge logically from the formalism. This model suggests that significant differences between placebo and homeopathy in blind RCTs would be found more frequently if in situ randomization/unblinding was used.
Keywords: Quantum probabilities; Entanglement; Contextuality; Non-local interactions